2013
DOI: 10.7314/apjcp.2013.14.3.1565
|View full text |Cite
|
Sign up to set email alerts
|

Cruciferous Vegetables: Dietary Phytochemicals for Cancer Prevention

Abstract: Relationships between diet and health have attracted attention for centuries; but links between diet and cancer have been a focus only in recent decades. The consumption of diet-containing carcinogens, including polycyclic aromatic hydrocarbons and heterocyclic amines is most closely correlated with increasing cancer risk. Epidemiological evidence strongly suggests that consumption of dietary phytochemicals found in vegetables and fruit can decrease cancer incidence. Among the various vegetables, broccoli and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(46 citation statements)
references
References 48 publications
0
46
0
Order By: Relevance
“…Interestingly, prevention and/or protection from chemical carcinogens by phytochemicals present in glucosinolate-containing cruciferous vegetables is of great interest because they may provide a safe and cost-effective strategy for combating cancer [5, 6**]. In this context, numerous epidemiological and pharmacological studies have revealed that the consumption of cruciferous vegetables has substantial potential for human cancer chemoprevention [7]. …”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, prevention and/or protection from chemical carcinogens by phytochemicals present in glucosinolate-containing cruciferous vegetables is of great interest because they may provide a safe and cost-effective strategy for combating cancer [5, 6**]. In this context, numerous epidemiological and pharmacological studies have revealed that the consumption of cruciferous vegetables has substantial potential for human cancer chemoprevention [7]. …”
Section: Introductionmentioning
confidence: 99%
“…It is generally accepted that consumption of cruciferous vegetables is inversely associated with the risk for variety of cancers, including CRC[4-8]. It is believed that glucosinolates, sulfur-containing phytochemicals, and their metabolic derivatives ( e.g ., isothiocyanates) play an important function in the cancer-chemopreventive role of cruciferous plants[9]. They act through multiple mechanisms in the prevention of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…This chemoprotective effect is closely related to isothiocyanates (ITCs), a group of hydrolysis products of glucosinolates, which are relatively unique in cruciferous vegetables [7, 8]. As one of the most studied ITCs, sulforaphane (4-methylsulfinybutyl isothiocyanate, SFA) was initially identified as the principal inducer of phase II enzymes [9] and has subsequently been shown to possess anticarcinogenic activities in many malignances [1015].…”
Section: Introductionmentioning
confidence: 99%